SPINE workshop on automated X-ray analysis: a progress report - Bahar, M; Ballard, C; Cohen, SX; Cowtan, KD; Dodson, EJ; Emsley, P; Esnouf, RM; Keegan, R; Lamzin, V; Langer, G; Levdikov, V; Long, F; et al. (International Union of Crystallography, 2006)
The Structural Proteomics In Europe (SPINE) consortium contained a workpackage to address the automated X-ray analysis of macromolecules. The aim of this workpackage was to increase the throughput of three-dimensional structures while maintaining the high quality of conventional analyses. SPINE was able to bring together developers of software with users from the partner laboratories. Here, the results of a workshop organized by the consortium to evaluate software developed in the member laboratories against a set of bacterial targets are described. The major emphasis was on molecular-replacement suites, where automation was most advanced. Data processing and analysis, use of experimental phases and model construction were also addressed, albeit at a lower level.